Military Human Resource Planning through Flow Network Modeling. Issue 2 (3rd April 2022) - Mazari Abdessameud, Oussama; Van Utterbeeck, Filip; Guerry, Marie-Anne
Abstract: Hierarchical organizations have to build the right human resource (HR) composition to fulfill their operational and strategic needs. One of the largest hierarchical organizations that face this challenge is the military organization. To tackle this challenge, managers rely on military HR planning that consists of strategic planning and operational planning. The general practice of focusing on the strategic planning then dealing with the operational planning could lead to an undesired manpower composition. Therefore, we propose an approach that allows simultaneous HR planning for both strategic and operational levels. Such simultaneous planning ensures building an adequate plan that considers the different aspects of personnel. We employ a flow network model to represent the military human resource system. To find an adequate solution that, we use mixed integer goal programming.